2015
DOI: 10.1177/0022034515608832
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Implant Therapy Analyzed in a Swedish Population

Abstract: Peri-implantitis is an inflammatory disease affecting soft and hard tissues surrounding dental implants. As the global number of individuals that undergo restorative therapy through dental implants increases, peri-implantitis is considered as a major and growing problem in dentistry. A randomly selected sample of 588 patients who all had received implant-supported therapy 9 y earlier was clinically and radiographically examined. Prevalence of peri-implantitis was assessed and risk indicators were identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
534
12
22

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(609 citation statements)
references
References 25 publications
(29 reference statements)
41
534
12
22
Order By: Relevance
“…The treatment group with the highest weight, being 1,578 implants (Derks et al., 2016), reported a prevalence of 25% with a mean bone loss of 0.7 mm, 61% of the implants showing BoP, and 17% of the implants with a PPD ≥ 6 mm. The smallest treatment group included 15 implants (Canullo et al., 2016) and detected no peri‐implantitis with a limited mean bone loss (0.2 mm) and 20% of the implants showing BoP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment group with the highest weight, being 1,578 implants (Derks et al., 2016), reported a prevalence of 25% with a mean bone loss of 0.7 mm, 61% of the implants showing BoP, and 17% of the implants with a PPD ≥ 6 mm. The smallest treatment group included 15 implants (Canullo et al., 2016) and detected no peri‐implantitis with a limited mean bone loss (0.2 mm) and 20% of the implants showing BoP.…”
Section: Resultsmentioning
confidence: 99%
“…Reflecting on the results presented in Table 6, it is obvious that reported prevalence figures are larger when the threshold is low. Using the same implant design, Swedish studies that applied a threshold bone loss of approximately 0.5 mm concluded that 13%–25% of the implants were affected (Derks et al., 2016; Ekfeldt, Furst & Carlsson, 2017). Thresholds of bone loss of 2–3 mm yield much lower prevalence in the order of 5%–10%.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, peri-implantitis is characterized by both, inflammation of the surrounding peri-implant tissues and loss of supporting bone beyond initial biological bone remodelling. Nonetheless recent investigations have recognized at least 7 definitions of peri-implantitis based on the extension and severity of the bone loss [2]. These interpretations of the peri-implant disease certainly reflect the multifactorial nature of the entity, displaying a multitude of clinical presentations.…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, se ha reportado en la literatura una asociación importante en la que las rehabilitaciones sobre implantes realizadas por un no especialista, es decir un odontólogo general presentaban un mayor riesgo de sufrir periimplantitis (53).…”
Section: Téticaunclassified